PENGARUH JUS SEMANGKA (Citrullus Vulgaris Schrad) TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI PRIMER - Lavintang, Mutiara; Erwin, Erwin; Dewi, Yulia Irvani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Current changes in patterns of disease that were originally dominated by infectious diseases turned to noncommunicable diseases such as hypertension. This study aims to determine the effect of watermelon juice (Citrullus Vulgaris Schrad) on the blood pressure of patients with primary hypertension. The design of this research is "Quasy experiment" with "Non-equivalent control group" which was divided into 17 respondents in the intervention group and 17 more respondents in the control group. The samples are 34 respondents taken by using purposive sampling technique by considering inclusion and exclusion criteria. The instrument used in both groups is the sphygmomanometer merk Gea. An intervention in form of watermelon juice was given to the intervention group 1 times a day as much as 350 ml for 1 week. The analyses used were univariate and bivariate analysis by applying dependent sample t-test and independent sample t-test. The results showed that the mean blood pressure before given watermelon juice was 146,80 / 88,48 mmHg, while the mean of blood pressure after given watermelon juice was 141,59 / 85,37 mmHg. The result of statistical test obtained p-value (0,000) < α (0,05).  It can be concluded that giving watermelon juice can help to decrease the blood pressure in a patient of primary hypertension. The results of this study can be an alternative to control blood pressure in primary hypertension.Keywords: blood pressure, hypertension, watermelon juice